Analysis of the Concept of Islamic Education with Religious Moderation Insight in the Book of Falsafah At-Tarbiyah Al-Islamiyyah by Majid Irsan Al-Kilani - Habibi, Debi Fajrin (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2023)
This research aims to explore the concept of Islamic education with the values of religious moderation contained in Majid Irsan Al-Kilani's magnum opus falsafah at-tarbiyah al-islamiyyah. Because what is studied is text in the form of data used as a source of research material, this research uses a library research approach or literature study. This research uses a content analysis approach model, emphasizing in-depth discussion of the content of information written in the book. This research tries to build on the theory of human relations with God, humans with fellow humans, humans with nature, humans with life, and humans with the afterlife built by Al-Kilani. The results of this study show that the values of religious moderation in Al-Kilani's educational concept are implied in several things; integration between science and religion, relationships that humans must build for the sake of harmonization, equality between humans and nature, and emphasis on the urgency of values in the concept of education. Education built on the concept of religious moderation insight will make students' understanding moderate, tolerant and able to build harmony with nature.